Membrane filter method for recovery of fecal coliforms in chlorinated sewage effluents. - Lin, S D (1976)
The standard one-step M-FC broth-membrane-filter procedure for recovery of fecal coliforms from chlorinated sewage effluents is much less effective than the multiple-tube (most-probable-number) technique. A two-step membrane-filter method, using a pre-enrichment technique with phenol red lactose broth and incubation at 35 degrees C for 4 h, followether 18+/-2 h, enhanced fecal coliform recovery from chlorinated effluents. The results of 126 comparisons using chlorinated effluents from five wastewater plants showed that fecal coliform recovery by using the two-step membrane-filter method is comparable to that using the multiple-tube procedure.